Investigation on network coded mimo-noma for two-way relay networks - Ngu, War Hlaing (2019)
The combination of Non-Orthogonal Multiple Access (NOMA) and Multi-input Multi-output (MIMO) approach has been considered as an assuring multiple access for the fifth generation (5G) technology. Without needing to sacrifice the spectral efficiency, the combination of MIMO-NOMA scheme with low-rate channel coding technique can be an assuring method for the requirement of the 5G network. The drawbacks for MIMO-NOMA based scheme is having interferences and problems in power control which can lead to bandwidth expansion. Precoding method during transmission can efficiently minimize the interferences and maximize the signal to noise ratio (SNR) at receiver. Thus, precoding method is proposed, and it has been applied MIMO-NOMA system. Most of the existing works on NOMA are based on the assumption of perfect Channel State Information (CSI) at the transmitter side which in reality, it is not easy due to either the estimation error or the feedback delay. Therefore, MIMO-NOMA system is investigated in imperfect CSI with Zero Forcing (ZF) and Maximum Ratio (MR). To fulfil the demands of higher rate of data transmission, power efficient forward-error correction (FEC) schemes which are Convolutional Codes, Reed-Solomon Codes (RS), Turbo Codes and Low-Density Parity Check (LDPC) codes are adopted as channel coding schemes. To obtain a more efficient system, Random Interleaved Differential Encoding with redundancy scheme with network coding (R-RIDE) is proposed for both sources and a relay node. LDPC decoding is done using bit-flipping, probability-domain, log-domain, and simplified Log-domain decoders. Simulation results shows that the MIMO-NOMA system has the greater performance than NOMA system alone. The proposed precoding method gives almost 28% higher capacity performance than the conventional scheme. Higher spectral efficiency is obtained by investigating MIMO-NOMA system with MR under imperfect CSI. Moreover, both Bit Error Rate (BER) and Average Mutual Information (AMI) of the proposed R-RIDE in LDPC codes greatly outperforms compared to the proposed R-RIDE of other codes. Furthermore, it can be concluded that LDPC-R-RIDE by using simplified log-domain decoding in MIMO-NOMA system yields approximately 47% better BER values than NOMA system alone. The transmission rate is increased 50% by applying two-way relay network.